Correlation between macroscopic and microscopic mechanical behavior of tuff material under uniaxial compression - Jin Linlin; Ma Hongfa; Yu Jiang; Wang Feng; Yin Dawei; Qu Xiao; Yang Yingsong; Tao Minghao (Journal of Materials Research and Technology)
The micromechanical properties and structures of minerals play a crucial role in shaping the macro-mechanical behaviors of rocks. Tuff, a volcanic rock widely used as a special building material, is notable for its low density, high porosity, and easy deformation, influencing its mechanical and failure characteristics. This study employed X-ray diffraction (XRD) and thin-section analyses to determine the primary mineral components of tuff, along with their micromechanical properties. Nanoindentation and uniaxial compression tests were conducted to investigate the interplay between macroscopic mechanical behavior, microscopic properties, and crack propagation patterns. In addition, the two-dimensional particle flow numerical model was constructed based on the PFC2D partition modeling method to analyze the evolution law of the internal structure of tuff from the perspective of mineral microstructure. The findings revealed that tuff predominantly comprises Anorthite, Dolomite, Clinopyroxene, and Matrix, ranked in hardness as Anorthite > Dolomite > Clinopyroxene > Matrix. Hard minerals, such as Anorthite, resisted and redirected crack propagation, whereas softer minerals, like Clinopyroxene, had minimal influence on crack dynamics. Crack formation around mineral boundaries resulted in sharp increases in acoustic emission (AE) counts and slight stress fluctuations, whereas the development of shear cracks within minerals stabilized AE counts over time. Energy evolution patterns from numerical simulations mirrored experimental observations, highlighting energy accumulation in the pre-peak phase and rapid dissipation post-peak. These insights into the mechanical behavior and energy dynamics of tuff provide valuable guidance for its application in construction and engineering projects.